Fuzzy Logic Approach for Prediction of Health Index of Feeder Cable Based on Partial Discharge Parameter - Hafizh Saftian; Misbakhul Fajri; Suprijadi Suprijadi (Green Publisher Indonesia, 2025)
PT PLN (Persero) as the main provider of electricity in Indonesia, has a strong commitment to improving the reliability of electricity distribution. This reliability is reflected through indicators such as SAIDI (System Average Interruption Duration Index), SAIFI (System Average Interruption Frequency Index), and ENS (Energy Not Served), which are caused by disturbances in the 20 kV extension. Preventive efforts to reduce interruptions are mitigated before interruptions occur by conducting an assessment of the 20 kV feeder cable. This assessment provides important variables that can be processed to predict the condition of the cable and determine the next repair steps. The application of data analysis methods such as Fuzzy Logic in processing technical variables such as PDIV (Partial Discharge Inception Voltage), PDEV (Partial Discharge Extinction Voltage) and Partial Discharge charge values can provide more accurate predictions than conventional calculations. The ability of Fuzzy Logic to overcome uncertain problems, results in another view in assessing the health condition of the repeater cable (Health Index). The results of the research are expected to provide more optimal results as an effort to reduce the frequency of faults to support the achievement of company performance.